Profile of non-invasive physical health indicators associated with cognitive performance in Chinese older adults: evidence from the China Health and Retirement Longitudinal Study - Xiyu Wei; Chao Li; Dongyu Liu; Jieyi Chen; Yumeng Ju; Jin Liu; Bangshan Liu; Yan Zhang (BMC Public Health)
Abstract Background Existing studies have indicated the potential role of non-invasive physical health indicators as an early detector of mild cognitive impairment (MCI) in older adults. However, evidence is lacking in determining the appropriate physical health indicators for early screening of cognitive decline in each domain. Therefore, the current study aimed to establish a comprehensive physical health indicators profile in association with cognitive performance. Methods The present study utilized a three-year longitudinal cohort design, with data from the China Health and Retirement Longitudinal Study (CHARLS). 4,869 participants aged 60–97 years from CHARLS wave 2015 and 2018 who were cognitively and physically healthy were included in analysis. Physical functions (BMI, grip strength, blood pressure, balance tests, course walking time, repeated chair stands, and pulmonary function) were objectively measured by physical tasks. Cognitive performance domains (general cognition, episodic memory, executive function, verbal fluency, orientation, and language-and-praxis) were measured through standardised interviews and cognitive tasks. Multiple linear regression models were conducted to explore the association between physical health indicators and cognitive performance. Subgroup analysis was conducted to identify sex-specific factors. Results Pulmonary function was identified as associated with all domains of cognitive performance in older adults (β ranged between 0.05 and 0.08). Right grip strength was also identified as an important factor associated with all cognitive domains except general cognition (β ranged between 0.04 and 0.12). Subgroup analysis revealed that the association between physical health indicators and cognitive performance is more pronounced in males than in females. Conclusions A profile of non-invasive physical health indicators associated with cognitive performance was established, which warrants future incorporation of non-invasive physical health indicators in early risk screening systems for MCI, enabling timely intervention and prevention in older adults. Future studies can delve deeper into the mechanisms underlying this full-dimensional relationship between physical and cognitive domains.